Exploring innovative pedagogical approaches: primary school EFL teachers’ utilization of teaching strategies - Belyihun Muchie Lakew; Abiy Yigzaw Filatie; Birhanu Simegn Chanie (Cogent Education, 2025)
English language teaching strategies play a crucial role in enhancing the practicality of language instruction within the classroom, where teachers and students actively engage. These strategies significantly impact the effectiveness of language teaching practices; however, they have not been directly examined in the context of Ethiopian primary schools. This study aimed to explore primary school EFL teachers’ teaching strategies for employment in EFL classrooms. It employed a descriptive survey research design with a mixed methods approach. Ten primary schools were selected conveniently, including 60 teachers. The selection of the participants was not random, but it was based on the accessibility of the schools and the inclusion of all English teachers. Classroom observation, questionnaire and document analysis were used to collect data. The quantitative data were analyzed in percentages and frequencies, whereas the qualitative data were analyzed using thematic, content, and factor analysis techniques. The findings revealed primary school English language teachers were not teaching English using innovative teaching strategies: cooperative learning, task-based learning, project-based learning, differentiated learning, problem-solving, critical thinking and technology integration. Hence, the alignment of teaching strategies with the syllabus of English is mismatched. Although there were challenges in employing innovative teaching strategies, teachers’ commitment was found to be less. They voiced concerns about the erosion of respect for the teaching profession, low salaries, and lack of incentives for best practices, insufficient resources, and autocratic leadership within schools. Therefore, it was concluded that primary school English language teachers were not employing innovative ELT strategies for effective language teaching in Ethiopia.